Craniotomy Tumor Removal for Brain Metastases of Hepatocellular Carcinoma : A Case Report - Barutu, Andri Josua; Hamzah, Zainy (Talenta Universitas Sumatera Utara, 2024)
Introduction: Brain metastases (BM) are the most frequent type of brain tumors in adults and are the leading source of neurological issues related to systemic cancers. Case Description: Female, 49 years old, presented with decreased consciousness that occurred since 1 month before admission. Weakness of the right limbs is found. CT scan abdomen with contrast show hepatic segment VIII infarction. histopathological examination of hepatic tissue biopsy with the results of hepatocellular carcinoma MRI brain shows multiple lesions suggestive of brain metastasis. Discussion: Patient was diagnosed with space occupying lesion on the frontotemporal dd brain metastasis dd orbital roof meningioma + multiple space occupying lesion intracranial on the left parietooccipital ec. brain metastasis + hepatocellular segment V, VI, VII, and VIII. Patients underwent craniotomy tumor removal to remove intracranial masses. The patient's postoperative condition showed improvement in the level of consciousness with GCS E4M5V3. Conclusion. Craniotomy tumor removal provides several advantages for managing patients with brain metastases of hepatocellular carcinoma. Keyword: Craniotomy, Brain Metastases, Hepatocellular Carcinoma